Two new species of the genus Tiwaripotamon Bott, 1970 (Crustacea, Decapoda, Brachyura, Potamidae) from Guangxi, China - Chen, Yuxin; Sun, Hongying; Pan, Da (Zootaxa, 2026)
Two new species of semiterrestrial freshwater crabs, Tiwaripotamon laibinense sp. nov. and Tiwaripotamon liuzhouense sp. nov., are described from karst landscapes in Guangxi, China. These crabs are characterized by their relatively long and slender ambulatory legs, an adaptation commonly associated with a semiterrestrial lifestyle. Both species are distinguished from their congeners by a combination of characters, notably the structure of the male first gonopod and features of the carapace. Estimates of Kimura two-parameter distances based on mitochondrial COI sequences support the recognition of the two new species. With these additions, the number of Tiwaripotamon species known from China increases to six, further highlighting the karst regions of southern China as a hotspot of freshwater crab diversity.